RE-IMAGINING YOUTH AND YAHOO PLUS: A CRITICAL STUDY OF RELIGIOUS IMPACT ON SOCIAL LIFE IN NIGERIA - Talabi, Joseph Moyinoluwa; Alao, Damilare Samuel; Ade-Johnson, Christiana Shade; Akinyosoye, Ayodele Joshua; Bello, Samson Adedapo; Talabi, Felix Olajide (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The rise of Yahoo Plus, which is a form of internet fraud blended with ritual practices, has emerged as a pressing social reality influencing Nigerian youth culture. Alongside this trend is the growing wave of atheism, as many young people increasingly question the relevance of organised religion in addressing socio-economic struggles. This study examines the intricate intersection of youth culture, religion, law, and deviance, highlighting how constitutional freedoms, religious narratives, and State institutions influence social life in the context of cybercrime and evolving belief systems. The central concern is the disconnection between the moral ideals of Nigeria's dominant religions and the lived realities of young people grappling with poverty, unemployment, and marginalisation. While religion has historically provided moral guidance, its perceived inadequacy in addressing present-day challenges has resulted in normalised fraudulent practices like Yahoo Plus and fuelled skepticism toward faith. However, Nigeria's Constitution guarantees freedom of religion (Section 38), and the Cybercrimes Act of 2015 criminalises online fraud. Nevertheless, weak enforcement and corruption undermine these provisions. Adopting an anthropological approach, the study draws on ethnographic insights, observations of youth practices, and analysis of cultural, legal, and religious discourses, supplemented by secondary data. Findings show that Yahoo Plus thrives not only on economic desperation but also on religious syncretism, while disillusionment with religious institutions drives youth toward atheism or alternative spiritualties. The study concludes by recommending reforms in religious engagement, empowerment initiatives, and stronger legal enforcement, underscoring the need to reimagine the relationship between faith, law, and youth culture in Nigeria.